PENGARUH DANA DESA, PRODUK DOMESTIK REGIONAL BRUTO DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI 23 KABUPATEN/KOTA PROVINSI ACEH - Qudri, Muhammad; Sari, Cut Putri Mellita (LPPM UNIMAL, 2023)
The purpose of this research is to determine the influence of village funds, gross regional domestic product and human development index on poverty in 23 regencies/cities of Aceh Province. Using a panel data approach from 2016 to 2022 in 23 Regencies/Cities of Aceh province. From testing the selected panel model, namely the Random Effect Model (REM), the research results show that village funds partially have a positive and significant effect on the number of poor people in 23 regencies/cities of Aceh Province, the GRDP variable has a significant positive effect on the number of poor people in 23 regencies/cities. Aceh Province, and the HDI variable has a significant negative effect on the number of poor people in 23 districts/cities in Aceh province. Simultaneous test results state that simultaneously the variables village funds, GRDP, and HDI influence the number of poor people in 23 districts/cities in Aceh province.